Association between sugar consumption, sociodemographic, anthropometric and biochemical profiles - Zorada Hattingh; Catharina J. Bester; Corinna M. Walsh (AOSIS, 2013)
Background: The increase in prevalence of coronary heart disease, type 2 diabetes, obesity and abnormal blood lipid levels has raised the question of a possible relationship between these conditions and the consumption of sugar.Objectives: This study investigated the sugar consumption of financially-restricted Black women in Mangaung, South Africa.Method: Five hundred women were selected randomly and divided into younger (25-34 years)and older (35-44 years) groups. Dietary intake, sociodemographic status, anthropometry and biochemical data were obtained. Total sugar (TS) and added sugar (AS) consumption were compared between older and younger women as well as sociodemographic, anthropometric and biochemical categories.Results: AS intake contributed 12% and 13% of total energy intake in younger and older women, respectively. AS consumption was higher in younger women living in brick houses and those who possessed a microwave oven. In older women, it was higher in husbandheaded households. Underweight women with the lowest body mass index had highersugar consumption than overweight and/or obese women. Women with a lower body fat percentage had a higher AS consumption than women with a high body fat percentage. Sugar consumption was significantly lower in younger women with elevated serum lymphocyte counts. TS and AS consumption was higher in younger women with elevated serum glucoselevels. Older women with elevated serum insulin had a significantly higher TS consumption compared to those with normal insulin concentrations.Conclusion: The amounts of TS and AS consumed by women in this observational study were unlikely to contribute to overweight and/or obesity.